2018
DOI: 10.15578/squalen.v13i3.355
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiles and Antioxidant Activity of Caulerpa racemosa with Different Handlings

Abstract: Metabolite profiles and antioxidant activity of Caulerpa racemosa extract with different handlings were investigated. Three different handlings during transportation were applied, namely samples chilled with ice, stored in liquid nitrogen and soaked in seawater. The different handling significantly affected the yield of ethanolic crude extracts and inorganic fractions but insignificantly to organic fractions. Different handlings resulted in differences of major fractions of C. racemosa extracts. Major fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The natural green pigment chlorophyll has been proposed as a functional food health supplement in recent years. Chlorophyll is the main green pigment component in the macroalga Caulerpa racemose (Sihono et al, 2018). Chlorophylls and flavonoids are the main components in C. racemosa that are responsible for antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The natural green pigment chlorophyll has been proposed as a functional food health supplement in recent years. Chlorophyll is the main green pigment component in the macroalga Caulerpa racemose (Sihono et al, 2018). Chlorophylls and flavonoids are the main components in C. racemosa that are responsible for antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on edible Caulerpa from the Binuangeun coast have been reported previously, i.e. metabolite (Januar, Wikanta, & Hastarini, 2004;Sihono, Tarman, Madduppa, & Januar, 2018) and nutrition profiles (Putri, Jusadi, Setiawati, & Sunarno, 2017;Suryaningrum & Samsudin, 2019) as well as antioxidant activities (Nursid et al, 2016;Sihono et al, 2018). However, studies on fatty acids, amino acids, heavy metals, and molecular identification of these seaweeds have never been reported yet.…”
Section: Introductionmentioning
confidence: 99%